2021
DOI: 10.21511/ppm.19(4).2021.40
|View full text |Cite
|
Sign up to set email alerts
|

Employee motivation and job satisfaction in family-owned businesses

Abstract: This study aimed to investigate the differences in motivational focus and sources of satisfaction between family and non-family employees in family businesses. Data from a questionnaire survey conducted between May and September 2021 were used to examine the relationship of work motivation between family and non-family employees. Data were collected via a questionnaire and interviews with 56 non-family employees and 148 family employees from family businesses of eight Slovak regions. To meet the stated aim, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Individuals who are emotionally and normatively more dedicated to their family companies have lower attrition intentions than those who exhibit continuous commitment (Dawson et al, 2015). Additionally, Mura et al (2021) discovered that family employees had a more balanced approach to economic gain and moral fulfillment due to their affective commitment. Zahra et al (2008) also found that, when paired with a stewardship mentality, affective commitment helps family companies to monitor and adjust to environmental changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals who are emotionally and normatively more dedicated to their family companies have lower attrition intentions than those who exhibit continuous commitment (Dawson et al, 2015). Additionally, Mura et al (2021) discovered that family employees had a more balanced approach to economic gain and moral fulfillment due to their affective commitment. Zahra et al (2008) also found that, when paired with a stewardship mentality, affective commitment helps family companies to monitor and adjust to environmental changes.…”
Section: Literature Reviewmentioning
confidence: 99%